Photo-elicitation in qualitative research - Pompe van Meerdervoort, Tracy (My University, 2006)
The aim of the study The aim of the study is to find an optimal research methodology that is both beneficial to qualitative researchers (regarding data quality and interviewee participation) and research participants (regarding enjoyment of the research process and means of expression). This takes the form of a comparison assessing the use of the visual method of photo-elicitation in qualitative interviews. Firstly, photo-elicitation interviews and standard qualitative interviews as two different methodologies are compared. In this study the research subjects are children, and as noted in Chapter 3, photo-elicitation is particularly applicable to young research subjects, as it tends to break down the communication barriers
Thesis (M. Tech. - Dept. of Visual Arts and Design, Faculty of Human Sciences)
Keywords: Photo-elicitation; Photography as research tool; Visual research; 779.723; Images, Photographic -- Research.